Analysis of Performance Management And Work Achievements of Agricultural Extenders Assisting For Agricultural Economic Improvement (PPEP) South Ogan Komering Ulu Regency - Caroline, Sevia; Munajat, Munajat; Oktarina, Yetti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This research aims to analyze the performance management of agricultural extension in organizing agricultural extension in South Ogan Komering Ulu Regency. The subjects of this research are agricultural instructors assisting agricultural economic improvement (PPEP), which is an agricultural instructor recruiting from the South Sumatra Province Governor's Program based on South Sumatra Governor Regulation Number 45 of 2020. The sampling method was carried out using a census where the entire population was used as a sample, namely 113 respondents in 19 sub-districts. The performance of extension workers is measured using a scoring method with measurement indicators by the Minister of Agriculture Regulation Number. 91/Permentan/OT.140/9/2013. The data analysis method used is Job Performance Value (NPK) analysis. The research results from the analysis show that the performance management of agricultural extension workers has a score with an average value for planning preparation of 4.70. Implementation of agricultural extension 3.61, while evaluation and reporting 4.87. The work achievement score has a score in the Fair category, namely 50%.